Benefits and Drawbacks of International Medical Elective Databases in Abroad Elective Research: A Narrative Review - Storz, Maximilian Andreas; Imafuku, Rintaro (Advances in medical education and practice, 2024)
Background: International medical electives (IMEs) are considered high-impact practice in global health education. Nevertheless, international medical elective (IME) research remains scarce, with only a few new publications appearing each year. The discrepancy between the many unanswered questions regarding IMEs and the lack of opportunities to perform research in this field has been further aggravated by the COVID-19 pandemic. Elective databases cataloguing structured IME reports/testimonies could offer a viable solution here. This narrative review provides a balanced and objective evaluation of the strengths and weaknesses of elective databases, summarizing their potential usefulness in IME research. Methods: The methodology employed was a multidisciplinary narrative review of the published and grey literature on databases cataloguing IME testimonies. Results: Elective databases offer numerous benefits to the IME researcher. Their size allows for large analyses, built on hundreds of equally structured elective testimonies. Pre-defined outcomes, such as the elective destination, elective discipline or duration, are queried in a standardized way, allowing for a broad set of research questions. Elective databases are usually open-access, not confined to a single university, and free to use. Most databases also offer user-friendly filter functions, permitting targeted analyses centered around a particular outcome. A major drawback is that reports are rarely verified. Subject to several forms of bias (eg, recall and reporting bias), elective databases may not be suitable for all types of research questions, and the report quality is often inhomogeneous. Above all, they rarely allow for an informational depth that may result from qualitative face-to-face interviews. Conclusion: Elective databases could be a valuable supplement to interview-based elective research, potentially allowing for larger and broader analyses not confined to single institutions. Keywords: international medical elective, abroad elective, medical education, global health, learning, research